Analysis of the Cross-Border E-Commerce Environment for Philippine Women-led MSMEs: Challenges and Opportunities - Jean Clarisse T. Carlos; Jovito Jose P. Katigbak; Jill Angeli V. Bacasmas (Philippine Institute for Development Studies (PIDS), 2022)
Operationalizing a Strengths, Weaknesses, Opportunities, and Threats (SWOT) Framework to process data gathered from an adapted diagnostic toolkit entitled "Women-Owned Businesses in Cross-border E-commerce: a Diagnostic Toolkit," this study reveals that regional and national policy landscapes have put utmost interest in promoting and fostering an enabling environment for WMSMEs and digitalization. However, there are gaps in public-private sector coordination, access to enabling and supportive programs such as financing and capacity building, awareness due to informality, and scaling-up and sustainability of their e-commerce businesses. Moreover, the results also show that the cross-border e-commerce environment is promising from the point of view of (a) networks, representation, and visibility, and (b) digital literacy, e-payments, e-commerce, and digital trade regulations. However, there are areas for improvement, such as in: (a) digital literacy, e-payments, and e-commerce and digital trade regulations; (b) discrimination on online platforms; (c) trade facilitation agreement; and (d) logistics and customs duties. Given the results of the diagnostic toolkit and SWOT, the authors identified key practical policy recommendations for consideration.
Keywords: 330; MSMEs; e-commerce; cross-border; trade; digitalization; women-led MSMEs